Performance Pay and Work Hours: US Survey Evidence - Benjamin Artz; John S. Heywood (Institute of Labor Economics (IZA), 2022)
We examine the hypothesis that performance pay increases work hours. If performance pay incentivizes greater hours, this could cause the demonstrated link between performance pay and poorer worker health. Using US survey data, we confirm greater work hours and an increased likelihood of long working hours for performance pay workers. This remains in worker fixed effect estimates and in worker with employer fixed effect estimates. The magnitudes remain sufficiently large to support the potential role of long hours as an intermediary between performance pay and reduced worker health. Despite managers being the most likely to both receive performance pay and work long hours, we show this association largely reflects sorting and not the behavioral response evident for other workers.
Keywords: J22; J33; 330; performance related pay; hours worked